2017
DOI: 10.4236/oalib.1104016
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Degradation Characteristics of Oil Degrading Bacterial Strain

Abstract: Objective: The aim of study is to obtain a strain which can effectively degrade oil. Methods: By enrichment, domestication and separation of culture from the sample which comes from Qianjiang Guanghua Oilfield, the pure culture (G-40) was selected from the medium supplemented with oil as the sole source of carbon. The G-40 was preliminarily identified and classified by morphological observation, physiological and biochemical determination and sequence analyses of 16S rDNA. Effects of temperature, pH, oil conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Our results are consistent with the earlier studies which have reported different species of Burkholderia capable of degrading variable aliphatic and aromatic hydrocarbons of petrol (Marin et al 2001;Chakraborty et al 2010;Mujahid et al 2015). Moreover, petrol hydrocarbon metabolizing Brevibacilli have also been reported in the literature (Xue et al 2006;Mnif et al 2011;Zhan et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the earlier studies which have reported different species of Burkholderia capable of degrading variable aliphatic and aromatic hydrocarbons of petrol (Marin et al 2001;Chakraborty et al 2010;Mujahid et al 2015). Moreover, petrol hydrocarbon metabolizing Brevibacilli have also been reported in the literature (Xue et al 2006;Mnif et al 2011;Zhan et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The optimal oil removal condition of G-94 was determined through biomass of petroleum degradation microorganism, not the oil removal rate. The reason why we use the biomass is that biomass is positively correlated with degradation rate and it is more convenient than oil removal rate [10].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were conducted in the oil medium described above with 0.5% oil (w/v) as sole carbon and energy source. Growth was monitored by measuring optical density at 420 nm with a TU-1900 spectrophotometer [10].…”
Section: Growth Studymentioning
confidence: 99%
See 2 more Smart Citations